Land transport policy in Singapore : an insight into the bus service. - Ong, Pei Sin. (2009)
A good land transport system is essential in ensuring the continuous economic growth of a country, especially a prosperous and populated city like Singapore. Such a system entails the infusion of both the policy in public transport and private transport to achieve a balance. Considering Singapore’s most serious constrain – land scarcity, it would be wise to focus on the public transport, instead of extending roads blindly.